Evaluation of Antidiabetic Activity of Novel Diarylsulfonylurea-Chalcone Hybrids in Streptozotocin-Induced Diabetic Models in Rats - Naidu, M. Akkulu (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: The aim of the study was to evaluate the diabetic activity of diarylsulfonylurea-chalcone hybrids on streptozotocin (STZ)-induced diabetic male albino rats. Materials and Methods: Diabetic activity of diarylsulfonylurea-chalcone hybrids at a dose of 10, 30, and 50 mg/kg body weight was evaluated. Adult male Swiss albino rats of six numbers in each group were undertaken for study and evaluated. Results: The results of in vivo hypoglycemic and antihyperglycemic activity of the synthesized diarylsulfonylurea-chalcone hybrid molecules (II.1-28) showed that all the compounds were found to possess moderate to potential ability to reduce blood glucose levels in normoglycemic and STZ-induced type 2 diabetic rats. Conclusions: The diarylsulfonylurea-chalcone hybrids have potent diabetic activity in the male albino rat.